Detection of a bibenzyl core scaffold in 28 common mangrove and associate species of the Indian Sundarbans: potential signature molecule for mangrove salinity stress acclimation - Sarkar, Bhanumati; Kotal, Hemendra Nath; Giri, Chayan Kumar; Mandal, Anup; Hudait, Nandagopal; Madhu, Nithar Ranjan; Saha, Subhajit; Basak, Sandip Kumar; Sengupta, Jhimli; Ray, Krishna (Frontiers in Plant Science, 2024)
Bibenzyl derivatives comprising two benzene rings are secondary plant metabolites with significant therapeutic value. To date, bibenzyl derivatives in the Plant kingdom have been primarily identified in bryophytes, orchids, and Cannabis sativa. The metabolic cost investment by plant species for the synthesis of these bioactive secondary metabolites is rationalized as a mechanism of plant defense in response to oxidative stress induced by biotic/abiotic factors. Bibenzyl derivatives are synthesized from core phenylpropanoid biosynthetic pathway offshoots in plant species. Mangrove and mangrove associate species thrive under extreme ecological niches such as a hypersaline intertidal environment through unique adaptive and acclimative characteristics, primarily involving osmotic adjustments followed by oxidative stress abatement. Several primary/secondary bioactive metabolites in mangrove species have been identified as components of salinity stress adaptation/acclimation/mitigation; however, the existence of a bibenzyl scaffold in mangrove species functioning in this context remains unknown. We here report the confirmed detection of a core bibenzyl scaffold from extensive gas chromatography-mass spectrometry and gas chromatographyflame ionization detection analyses of 28 mangrove and mangrove associate species from the Indian Sundarbans. We speculate that the common presence of this bibenzyl core molecule in 28 mangrove and associate species may be related to its synthesis via branches of the phenylpropanoid biosynthetic pathway induced under high salinity, which functions to detoxify reactive oxygen species as a protection for the maintenance of plant metabolic processes. This finding reveals a new ecophysiological functional role of bibenzyls in unique mangrove ecosystem.